Chemical Transformation Induced Core–Shell Ni2P@Fe2P Heterostructures toward Efficient Electrocatalytic Oxygen Evolution - Huijun Song; Jingjing Li; Guan Sheng; Ruilian Yin; Yanghang Fang; Shigui Zhong; Juan Luo; Zhi Wang; Ahmad Azmin Mohamad; Wei Shao (Nanomaterials, 2022)
The oxygen evolution reaction (OER) is a crucial reaction in water splitting, metal–air batteries, and other electrochemical conversion technologies. Rationally designed catalysts with rich active sites and high intrinsic activity have been considered as a hopeful strategy to address the sluggish kinetics for OER. However, constructing such active sites in non-noble catalysts still faces grand challenges. To this end, we fabricate a Ni2P@Fe2P core–shell structure with outperforming performance toward OER via chemical transformation of rationally designed Ni-MOF hybrid nanosheets. Specifically, the Ni-MOF nanosheets and their supported Fe-based nanomaterials were in situ transformed into porous Ni2P@Fe2P core–shell nanosheets composed of Ni2P and Fe2P nanodomains in homogenous dispersion via a phosphorization process. When employed as the OER electrocatalyst, the Ni2P@Fe2P core–shell nanosheets exhibits excellent OER performance, with a low overpotential of 238/247 mV to drive 50/100 mA cm−2, a small Tafel slope of 32.91 mV dec−1, as well as outstanding durability, which could be mainly ascribed to the strong electronic interaction between Ni2P and Fe2P nanodomains stabilizing more Ni and Fe atoms with higher valence. These high-valence metal sites promote the generation of high-active Ni/FeOOH to enhance OER activity.